(untitled) (Global Journal of Medical Research, 2020)
Porpoises, infected by Cetacean Morbillivirus from the feces of humpback whales in the East Sea, swam along the Yangtze River to reach Dongting Lake. Infected porpoises could be stranded and moved to Huanan Seafood Wholesale Market. Wuhan is low-lying and susceptible to flooding from the Yangtze River. Agricultural water in Hubei should prevent the harmful algal blooms for clean water. Sterilization by ultraviolet is recommended in air, water and confirmed patient with dialyzer to recover the Wuhan coronavirus disaster. The vaccine can be developed by culturing blood from CeMV infected porpoises in the Yangtze River or Dongting Lake, along with Wuhan coronavirus confirmed patient blood. Existing MMR Vaccine can be applied to cure high levels of UVB radiation on the Earth. Due to 11 years cycle of the sunspot number, there can be another dangerous outbreak at Dongting Lake with millions of migratory birds in China in coming years between 2030 and 2032.